Peningkatan Kapasitas Pokdarwis Melalui Pemaanfaatan Teknologi Informasi Untuk Pengembangan Wisata Desa Lebakmuncang Bandung Selatan - Jaelani, Achmad; Afrina Sari; Winaya Purwanti; Luthpiyah Juliandara; Dipa Teruna Awaludin (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The Pokdarwis of Lebakmuncang Village is a group of community leaders participating in the tourism village development program in South Bandung Regency. To unlock the tourism potential of Lebakmuncang Village, which includes stunning natural beauty, unique cultural heritage, and distinctive local crafts, it is essential to provide training and counseling. This activity uses a descriptive method, namely providing counseling and training to Pokdarwis members. Data analysis is carried out through four stages: collection, simplification, presentation, and verification of information. However, despite its significant potential, these attractions have not been fully utilized to support the economic growth of the local community. Challenges Faced by Pokdarwis in Developing Tourism Potential include: 1) Lack of Digital Understanding and Skills Limited knowledge about using digital tools for tourism promotion and management; 2) Conventional Promotion Methods Heavy reliance on traditional forms of marketing that have a limited reach; 3) Absence of an Integrated Tourism Information System Lack of a centralized platform to present comprehensive tourism information. The primary goal of coaching Pokdarwis is to help them recognize the potential of Lebakmuncang Village as a promising tourist destination and to empower them to share this vision with the broader community, which serves as a vital resource in village tourism development. Training and Counseling Program The training and counseling sessions were conducted over two days, from July 6-7, 2024. The results of these sessions were significant Increased Participation, Improved Financial Management, Adoption of Modern Packaging Technologies. Expanded tourism promotion reach with the adoption of digital tools such as social media, websites, and digital tourism platforms, the reach of tourism promotions has significantly expanded, attracting visitors from outside the region. This more structured and measurable approach has led to a noticeable increase in tourist visits.